2015
DOI: 10.1016/j.micromeso.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Potential new biocatalysts for biofuel production: The fungal lipases of Thermomyces lanuginosus and Rhizomucor miehei immobilized on zeolitic supports ion exchanged with transition metals

Abstract: Nanozeolite NaX ion exchanged with different transition metals (Mn 2+ ,Cu 2+ , Co 2+ , Zn 2+ , Ni 2+ ) was used as a solid support for the immobilization of the lipases of Thermomyces lanuginosus (TLL) and Rhizomucor miehei (RML). The nanozeolite-enzyme complexes were used as heterogeneous catalysts for the transesterification reaction of palm oil to fatty acid ethyl esters (FAEEs). The most relevant results were obtained with the Thermomyces lanuginosus enzyme immobilized on nanozeolitic supports ion exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 75 publications
3
23
0
Order By: Relevance
“…5). The important role played by nickel in enzyme immobilization and enzymatic activity has been reported previously [44,71] and was also observed here for the nanozeolite supports ion-exchanged with nickel.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…5). The important role played by nickel in enzyme immobilization and enzymatic activity has been reported previously [44,71] and was also observed here for the nanozeolite supports ion-exchanged with nickel.…”
Section: Resultssupporting
confidence: 87%
“…Transesterification of palm oil to FAEEs using lipases of Thermomyces lanuginosus (TLL) and Rhizomucor miehei (RML) immobilized on nanosized NaX zeolite (FAU) ionexchanged with different transition metals has shown positive results. This has encouraged further synthetic and catalytic studies of enzyme-nanozeolite complexes with supports derived from different zeolite structures, and their application in the catalytic conversion of different non-edible biomasses to biodiesel [44]. Nev-ertheless, careful analysis of the literature shows that there have been no systematic studies describing the chemical modulation of nanozeolite support surfaces using chemical modifiers such as the alkoxysilane molecule (3-aminopropyl)trimethoxysilane (APTMS), with crosslinking using glutaraldehyde (GA), and the effects on the nanozeolite-enzyme complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For efficient catalysis and yield, the immobilization material must be selected carefully based on its robustness, biocompatibility and recoverability (Temocin et al., 2018). Over the years, lipase immobilization on various support materials such as silica gel particles (Lee et al., 2006; Yang et al., 2010), macroporous resin (Yang et al., 2006), silica nanoparticles (Babaki et al., 2016), nanozeolites (Vasconcellos et al., 2015), carbon nanotubes (Fan et al., 2016), hybrid nanospheres (Verri et al., 2016) and chitosan microspheres (Palla et al., 2011) have been investigated for various uses. It has been reported that lipases immobilized on hydrophobic support materials show better catalytic properties than hydrophilic supports (Petkar et al., 2006; Wang et al., 2006).…”
Section: Enzymatic Synthesis Of Opomentioning
confidence: 99%
“…Also, Khasanov et al, have reported a study on the catalytic activity of fungal lipases derived from Oospora lactis , Penicillium sp., and R. microsporus . Further, fungal lipases derived from R. miehei and T. lanuginosus were studied for their immobilization on nanozeolite supports …”
Section: Sources Of Lipasesmentioning
confidence: 99%
“…Further, fungal lipases derived from R. miehei and T. lanuginosus were studied for their immobilization on nanozeolite supports. 116 Yeast Lipases. Yeast lipases constitute a very important source of lipases given their unique attributes in addition to their ease of culture that make them sought-after by many industries such as pharmaceutical, chemical, biodiesel, etc.…”
Section: Microbial Sourcesmentioning
confidence: 99%